Post-Surgical Pain Management in Oral Surgery - Abdul Wahed; Hammad, Jahangir; Khan, Attal; Zoina; Jan, Rahim; Alam, Maqbool (Indus Journal of Bioscience Research, 2025)
Background: An essential part of oral surgery is post-operative pain management, which affects patient satisfaction and recovery results in addition to patient comfort. This study examines post-operative pain management techniques that use both pharmaceutical and non-pharmacologic approaches, with a focus on patient outcomes, adverse effects, and overall effectiveness. Objective: to determine the most popular approaches and the variables affecting their choice, as well as to assess the efficacy and patient satisfaction of the different pain management strategies utilized following oral surgery. Methods: This six-month qualitative study was carried out at a Quetta tertiary care facility. Semi-structured interviews were conducted with a purposive sample of 100 patients who had oral surgery. Patient-reported experiences with pharmacologic (NSAIDs, acetaminophen, opioids) and non-pharmacologic (cold therapy, TENS, laser treatment, education) pain management techniques were evaluated using thematic content analysis. Results: The most commonly utilized analgesics were NSAIDs (72%) and acetaminophen (65%), with combination therapy being used for 54% of patients. The most popular non-pharmacologic approach was cold therapy (66%). The majority of patients (86%) said they were happy with the way their pain was managed. Although 55% of respondents reported no negative effects, common side effects included tiredness (19%) and stomach discomfort (22%). Conclusion: A multimodal strategy that includes patient-centered care is necessary for effective post-operative pain control in oral surgery. NSAIDs continue to be the most common analgesics, although non-pharmacologic approaches, despite their underutilization, have the potential to improve satisfaction and recovery. In order to maximize results and minimize risks, the study promotes a stronger focus on patient education, integrated pain management techniques, and customized treatment regimens.